Improving Student Learning Outcomes in Social Sciences Lessons on Economic Business Types Through Role Playing Models - Mardhika, Atmira Satya (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is an effort to improve student learning outcomes in social studies lessons on economic business types by using a roleplaying learning model for VE class students at Innovative Ta'mirul Islam Elementary School. This research is classified as a type of CAR carried out in the VE class of Ta'mirul Islam Innovative Elementary School with a total of 24 students consisting of 12 males and 12 females. The steps taken in this PTK include planning, implementing, observing and reflecting. The research results show that the use of the roleplaying method can improve student learning outcomes well. This can be seen from the increase in the average class and grades that meet the KKM. Pre-Cycle learning had a class average of 68.12 with learning completeness of 33.33%, Cycle I increased to 79.6 and learning completeness was 75.00%, Cycle II increased again to 86.87 with learning completeness of 91.67%. Therefore, it can be concluded that the use of the roleplaying method can improve the learning outcomes of VE class students at Ta'mirul Islam Innovative Elementary School.